Critical Analysis of International Collaboration, Crisis Management, And Policy Development In Global Health - AL HARTH, HUSSEIN HASSAN SALEH; ALRABIE, MOHAMMED ALI NAJI; ALDAGHMAN, YASIR MASOUD ALI; AL RAGEEP, MESHAL MOHAMAD; ALWAELI, ABDULLAH MUZHIR; ALRUBUO, TURKI ABDULLAH; ALYAMI, NORAH SALEM HAMAD; BALHARITH, ABDULLAH SALEH ALI; AL SHARIAH, HADI MUHAMMAD HUSSEIN; AL EDALL, ABDULLAH HUSSAIN YAHYA (Journal of Ecohumanism, 2024)
As it is witnessed in pandemics, natural disasters, and other outbreaks of diseases, health management has necessitated international cooperation. To achieve the above objective, this paper critically evaluates international collaboration, crisis management, and policy in global health. Devoted to the analysis of present and previous global dangers like COVID-19, the paper investigates the performance of multiple international health frameworks and the difficulties in implementing them. In addition, the study looks into the specified context to review the contribution of policymaking in such crises and the remaining voids in international health administration. In an attempt to make practical suggestions on how international relations in health should be enhanced to accommodate future crises, this paper presents a synthesis of the resources of literature, data, and case studies available on the subject.